Cardiotoxicity of non-cardiovascular drugs - Minotti, Giorgio (Chichester, West Sussex : Wiley, 2010)
"First book to deal with this important area of adverse drug reactions -- cardiotoxicity is one of the major forms of toxicity seen in drugs and it accounts for most drug recalls and delays experienced in regulatory approvals. Covers four important therapeutic classes: psychoactive drugs; anticancer drugs; non-steroidal anti-inflammatory drugs; and anti-retroviral drugs. - Emphasis on the preclinical screening of drug cardiotoxicity, to enable drug developers to test for this toxicity before starting expensive clinical trials"--Provided by publisher.
Machine generated contents note: List of Contributors -- 1. Mitochondrial Dysfunction In Cell Injury and Cardiotoxicity -- Fabio Di Lisa, Martina Semenzato, Andrea Carpi, Sara Menazza, Nina Kaludercic, Roberta Menabò, Marcella Canton -- 2. Cardiovascular Liabilities of Drugs: Regulatory Aspects -- Claudio Arrigoni -- 3. Cellular Mechanisms, Molecular Targets, and Structure-Function Relationships In Drug-Induced Arrhythmias: The Case Of Antihistamines, Psychoactive Drugs, and Antimicrobial Agents -- Maria Virginia Soldovieri and Maurizio Taglialatela -- 4. Cardiovascular Toxicity of Antitumor Drugs: Dimensions of the Problem in Children -- Rebecca Scully, Louis Pruitt, Steven E. Lipshultz -- 5. Cardiovascular Toxicity of Antitumor Drugs: Dimension of the Problem in Adult Settings -- Joseph R. Carver and Chaitali J. Desai -- 6. Diagnostic Aspects of Cardiovascular Toxicity of Antitumor Drugs -- Michael S. Ewer, Thomas M. Suter -- 7. Cardiovascular Toxicity of Antitumor Drugs: Translating Molecular Mechanisms into Clinical Facts -- Pierantonio Menna, Emanuela Salvatorelli, Carlo Salsano, Luca Gianni*, and Giorgio Minotti -- 8. NSAID Action and the Foundations for Cardiovascular Toxicity -- Anna L. Blobaum and Lawrence J. Marnett -- 9. Cardiovascular toxicities of NSAIDS: Epidemiologic aspects -- Antonio González-Pe;rez, Luis Alberto Garci;a Rodriguez -- 10. Cardiovascular Toxicities of Life-Saving Drugs: Antiviral Therapy -- James J. Kohler & William Lewis.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Cardiovascular toxicology; Electronic books